Efforts to Increase Student Concentration in Mathematics Learning Difficulties Using Wordwall Application Media for Class IV Elementary School Students - Anggreini, Nurul; Putri, Dwi; Indriani, Dea; Adinata, Hasrudi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aimed to improve the concentration and engagement of fourth-grade students in mathematics learning by utilizing the Wordwall application as an interactive learning medium at SDN 064/VII Sukasari II Sarolangun. The study employed a Classroom Action Research (CAR) approach, conducted in two cycles, from October to December 2024. The results from Cycle 1 showed an increase in student enthusiasm and engagement, but learning mastery did not meet the success criteria. In Cycle 2, after adjustments to teaching strategies, significant improvements were observed. The percentage of students who achieved the Minimum Mastery Criteria (KKM) increased from 78.26% to 86.95%, and 90% of students actively participated in the learning process. The findings suggest that Wordwall effectively enhances student concentration, increases motivation, and creates a more interactive and enjoyable learning environment. It is recommended that teachers use Wordwall to improve student focus and engagement, particularly in mathematics education.